The Effectiveness of Combining Visual Art Activities and Physical Exercise for Older Adults on Well-Being or Quality of Life and Mood: A Scoping Review. (December 2019) - Roswiyani, Roswiyani; Kwakkenbos, Linda; Spijker, Jan; Witteman, Cilia L.M.
Visual art activities and physical exercise are both low-intensity and low-cost interventions. The present study aims to comprehensively describe published literature on the effectiveness of a combination of these interventions on well-being or quality of life (QoL) and mood of older adults. Embase, CINAHL, Ovid Medline (R), PsycINFO, and Web of Science databases were searched for studies published between 1990 and 2015 that evaluated interventions combining visual art therapy and exercise for people aged 50 years or older with at least one resultant well-being or QoL or mood outcome. We found 10 studies utilizing different combination programs and outcome measures, and most had small sample sizes. Seventy percent of the studies reported that combining both interventions was effective in improving well-being or QoL and mood in older adults. Future studies are, however, requisite to investigate whether in the respective population such a combination is more effective than either of the interventions alone.